Evaluating the Impact of Increasing General Education Teachers' Ratio of Positive-to-Negative Interactions on Students' Classroom Behavior. (April 2017) - Cook, Clayton R.; Grady, Erin A.; Long, Anna C.; Renshaw, Tyler; Codding, Robin S.; Fiat, Aria; Larson, Madeline
The aim of this study was to isolate and evaluate the impact of increasing teachers' ratios of positive-to-negative interactions with their students. Training teachers on the 5:1 ratio was evaluated using a randomized-block pre–post control design with general education classroom teachers ( N = 6) that were characterized by a higher ratio of negative-to-positive interactions between students, as well as low academic engagement and high disruptive behaviors. Teachers in the intervention group were trained on the 5:1 ratio, instructed to wear a device that prompted them on a VI 5-min schedule to deliver specific praise, approval statements, and positive non-verbal gestures to specific students exhibiting expected behaviors or the entire class as a whole, and completing a self-monitoring chart to increase their awareness of their ratios. Results revealed that students in the intervention group displayed significantly fewer disruptive behavior problems and higher academic engaged time when compared with students in control classrooms. Social validity results also revealed that teachers found the strategy feasible, acceptable, and effective. Limitations of this research, including the small-scale nature of this study, and future directions for teacher training, retention, and schoolwide universal prevention are discussed.